Herbicide Evaluation for Control of Kochia and Palmer Amaranth in Teff Grass - J. D. Holman; C. Thompson; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2015)
Eleven postemergence herbicide treatments were applied to teff grown for forage to evaluate Palmer amaranth and kochia control, as well as crop tolerance. Effective Palmer amaranth control was achieved with all herbicide treatments, while less than satisfactory kochia control was obtained with atrazine and Harmony. Clarity, 2,4-D, and Huskie applied alone appeared to control kochia, but kochia density was low in the plots. Had the kochia population been higher, similar efficacy ratings may have been attained. Huskie or atrazine caused the most injury to teff. The first harvest suggests these herbicides reduced forage yield to less than 3,000 lb/a.
Keywords: weed science; weed control; teff; kochia; Palmer amaranth; herbicide; atrazine; Harmony; Clarity; 2; 4-D; Huskie